The Water Horses of Loch Ness by Roland Watson - Bauer, Henry (Journal of Scientific Exploration, 2022)
In The Water Horses of Loch Ness, Roland Watson presents a significant and original contribution to methods for evaluating and interpreting traditional stories and folklore. Are Nessies real animals, or are they an entrepreneurial tourist trap capitalizing on folklore? Or are they perhaps supernatural entities? Each of those hypotheses has its adherents, and they each offer evidence. Most cryptozoologists pursue the real-animals hypothesis. However, a British novelist and former PR executive confessed to inventing the creatures to help the hotel industry (Bauer, 1986: 3-4), and an Italian journalist later claimed, separately and independently, to have invented the creatures [2]. Ted Holiday (1973), among others, envisaged a supernatural explanation. In any event, it surely seems relevant that Scots folklore features such creatures as Water Horses, Water Bulls, Water Kelpies, to which are attributed a variety of characteristics. But relevant in what way? How to assess what lies at the root of this folklore?